PENGARUH PEMBERIAN PUDING TEMULAWAK TERHADAP KESULITAN MAKAN PADA BALITA USIA 2-5 TAHUN DI WILAYAH KUTABUMI TAHUN 2021 - Kartika Swarnasari Kusuma; Nurry Ayuningtyas Kusumastuti Kusumastuti (Nusantara Hasana Journal, 2022)
Difficulty eating is a refusal of food so that it is not able to meet nutritional needs. Food refusal is based on food senses such as the appearance of food, the smell and taste of food and fears that occur while eating such as fear of swallowing food. One of the causes of eating difficulties in toddlers is picky eating, eating disorders, eating disorders in the mouth, and eating disorders in toddlers. One of the traditional medicines that can increase and improve the lack of appetite in children is temulawak. Temulawak contains the active substance curcumin which can increase the activity of digestive enzymes, so it will increase the child's appetite. The purpose of this study was to determine whether there was an effect of giving temulawak pudding on eating difficulties in toddlers aged 2-5 years. Method: The method used in this research is Pre Test Post Test Control Group Design. The sample in this study were toddlers aged 2-5 years at Perum Taman Buah 1 totaling 30 toddlers where 15 toddlers were given intervention and 15 toddlers were not given intervention. The sampling technique used is purposive sampling. Collecting data in this study using a questionnaire difficulty eating. In this study using the Mann-Whitney test, the average value before giving temulawak pudding was 36.87 and the average value after giving temulawak pudding was 20.93 and p-value was 0.000 (<0.001). There is a sufficient influence between the effect of giving temulawak pudding on eating difficulties in toddlers aged 2-5 years in the Kutabumi region.